How to Measure the Elderly’s Quality of Life in European Rural Areas? A Look at Poland - Mariola Zalewska; Zofia Sawicka (Barometr Regionalny)
The study is aimed at identifying the information gap in the field of quality of life research, with regard to the quality of life and rural development indicator systems. In addition, selected indicators particularly important for the elderly in the European Union rural areas are compared. The existing indicator systems which enable an international comparison have a wide scope. Their disadvantages are that only some of them are classified by rural and urban areas (Eurostat indicators), that they are selected and presented in accordance with the current EU policy targets (rural development indicators) and that data are aggregated up to the NUTS 3 level (subregional), which makes it difficult to use this information for strategic planning at the local level. Among the three selected measures of quality of life of the elderly in rural areas, Poland ranks well below the average in access to health care.